2010
DOI: 10.1007/s00246-009-9622-z
|View full text |Cite
|
Sign up to set email alerts
|

Moderate Sedation for Echocardiography of Preschoolers

Abstract: Preschoolers frequently require sedation for echocardiograms. This study compared various sedation drugs at the authors' institution, as well as the charges for moderate versus deep sedation. From 2001 to 2007, sedation was administered to 703 patients ages 2 to 4 years. Four drug regimens were used: chloral hydrate (CH), chloral hydrate with diphenhydramine (CH + D), chloral hydrate with hydroxyzine hydrochloride (CH + H), and midazolam. The mean onset of sedation was 37 min, and the mean duration of sedation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 11 publications
1
10
1
Order By: Relevance
“…They are also used for treatment of serotonin syndrome, anxiety, acute agitation, akathisia, and migraine headaches. 1,18,[86][87][88] Dimenhydrinate, diphenhydramine, meclizine, and promethazine block the histaminergic signal from the vestibular nucleus to the vomiting center in the medulla. They are used for prevention and treatment of nausea and vomiting during pregnancy, chemotherapy, and the postoperative period and for prevention and treatment of motion sickness, vertigo, and related disorders.…”
Section: Second (New)-generation H 1 -Antihistaminesmentioning
confidence: 99%
See 1 more Smart Citation
“…They are also used for treatment of serotonin syndrome, anxiety, acute agitation, akathisia, and migraine headaches. 1,18,[86][87][88] Dimenhydrinate, diphenhydramine, meclizine, and promethazine block the histaminergic signal from the vestibular nucleus to the vomiting center in the medulla. They are used for prevention and treatment of nausea and vomiting during pregnancy, chemotherapy, and the postoperative period and for prevention and treatment of motion sickness, vertigo, and related disorders.…”
Section: Second (New)-generation H 1 -Antihistaminesmentioning
confidence: 99%
“…[76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91] Atopic dermatitis. Histamine acts as a pruritogen through H 4 -receptors in patients with atopic dermatitis, and other mediators, including IL-31 and other cytokines, play an important role.…”
Section: Second (New)-generation H 1 -Antihistaminesmentioning
confidence: 99%
“…Studies in dentistry10 12 and echocardiography11 also demonstrated savings for conscious sedation compared with GA. The paediatric dentistry study by Jameson et al 10 showed the mean cost of GA per child to be £359.91, 46.6% more costly than conscious sedation (£245.47) using combined techniques such as inhaled nitrous oxide with sevoflurane or intravenous agents such as midazolam and fentanyl.…”
Section: Discussionmentioning
confidence: 98%
“…11,12,13 Higher doses of oral midazolam have been used in pediatric dentistry, echocardiography and in neuro-imaging studies as well. 2,13,14 We chose the dose of 0.75 mg/kg oral midazolam for our study.…”
Section: Discussionmentioning
confidence: 99%